2016
DOI: 10.1007/s11746-016-2879-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fatty Acetoacetates Under Microwave Irradiation Catalysed by Sulfamic Acid in a Solvent‐Free System

Abstract: of polymers, drugs and biologically active compounds [1][2][3]. They have also been studied as biofuel additives [4].Using acetoacetates as the building blocks in multicomponent reactions (MCR) [5] yields several different structures based on the dihydropyridinone (DHPM) or dihydropyridine (DHP) skeleton, which creates an extensive library of compounds with various biological activities [6-10]. MCR have been recognized for their high convergence, atomic economy and operational simplicity and are emphasized as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Initially, fatty alcohols and fatty acids were used as precursors to synthesize fatty b-ketoesters (FBKEs) using previously reported methods. 29,30 FBKEs 1a, 1b and 1c were synthesized by the transesterication of methyl acetoacetate from palmitic (C16:0), stearic (C18:0), and oleyl (C18:1) alcohols, respectively. At the same time, the FBKE precursors 2a, 2b and 2c were synthesized via Meldrum's acid acylation with the corresponding fatty acids, followed by a decarboxylation step using methanol (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, fatty alcohols and fatty acids were used as precursors to synthesize fatty b-ketoesters (FBKEs) using previously reported methods. 29,30 FBKEs 1a, 1b and 1c were synthesized by the transesterication of methyl acetoacetate from palmitic (C16:0), stearic (C18:0), and oleyl (C18:1) alcohols, respectively. At the same time, the FBKE precursors 2a, 2b and 2c were synthesized via Meldrum's acid acylation with the corresponding fatty acids, followed by a decarboxylation step using methanol (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Weber et al have recently reported the synthesis of long chain acetoacetates via sulfamic acid catalysis under solvent-free conditions ( Table 66 ). 150 Using microwave irradiation, the reaction time was reduced from 6 hours to 13 minutes. The yields obtained via conventional heating or microwave irradiation were comparable.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%